Microbiological Quality and Physico-chemical Properties of Bore-Hole Water from Stored Water Tanks in Selected Hostels in Ifite-Awka, Nigeria - Okafor, Ugochukwu Chukwuma; Anastasia, Onwugbenu Nneoma; Dike, Umeoduagu Nnamdi (Tropical Aquatic and Soil Pollution, 2023)
The microbiological and physicochemical properties of bore-hole waters from water reservoirs in selected hostels in ifite-Awka metropolis were evaluated. Five (5) bore-hole water samples from stored-water tanks were evaluated to ascertain the physicochemical parameters, presence and population of different bacterial and fungal groups. Total heterotrophic bacterial (THC) counts ranged from 1.20x103 cfu/ml to 6.5x103 while the fungal counts spanned from 2.5x103 cfu/ml to 8.9x103 cfu/ml. Bacteria obtained from the borehole waters include Salmonella spp., Escherichia coli and Shigella spp. E. coli was the most prevalent with MPN 380/100 ml of water reported in sample A while Shigella sp. was the least prevalent with MPN 130/100 ml of water reported in samples B and E. Fungal isolates obtained include Aspergillus species, Candida species, Acremonium species and Cladosporium species. E. coli and Aspergillus spp. were predominant than other isolates. The pH ranged from 6.65 to 7.47; hardness ranged from 92 mg/l to 156 mg/l and Iron concentration ranges from 0.267 ppm to 0.378 ppm, phosphate contents ranged from 2.375 to 6.125 while Nitrate contents ranged from 1.071 to 6.214. The presence of these organisms in water meant for municipalities indicates faecal contamination. This calls for improved sanitary conditions of reservoir tanks in these locations and beyond.